E-MSMEs (SMALL AND MEDIUM MICRO ENTERPRISES) BASED ON ANDROID TO INCREASE SALES OF BENI SCROLL ART - Triana Sri Gunarti; Baibul Tujni; Imam Solikin (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2022)
Abstract: Micro, Small and Medium Enterprises (MSMEs) are business entities or individuals that have productive activities and fulfill the criteria for micro-enterprises. The development of the economic sector in Indonesia is also influenced by MSME businesses. Beni Scroll Art is an MSME engaged in the sale of handicrafts such as making miniature amperes, trophies made of wood, bird statues made of wood and so on. This research is a development of research that previously discussed the use of website-based information technology which was developed into android-based information technology. Android-based sales applica-tion development is more effectively used for the community in the buying and selling process because it is more familiar in the community. Therefore, the system development carried out by researchers is an Android-based application in the sales process and to in-crease sales. The method used in developing this android application is a prototype with several stages of Communication, Quick Plan, Modeling and Quick Design, Quick Design, Construction of Prototype, and Deployment Delivery and Feedback. The purpose of this research is to simplify sales, increase sales, and make the sales process more effective and efficient.            Keywords: applications; android; sales; SMEs  Abstrak: Usaha Mikro Kecil Menengah (UMKM) merupakan badan usaha atau perseorangan yang mempunyai kegiatan produktif serta memenuhi kreteria dalam usaha mikro. Perkembangan bidang ekonomi di Indonesia juga diperngaruhi oleh usaha UMKM. Beni Scroll Art merupakan UMKM yang bergerak dibidang penjualan keterampilan tangan seperti pembuatan miniature ampere, piala dengan bahan dasar kayu, patung burung dengan bahan dasar kayu dan sebagainya. Penelitian ini merupakan pengembangan dari penelitian yang sebelumnya membahas pemanfaatan teknologi informatika berbasis website dikembangkan menjadi teknologi informasi berbasis android. Pengembangan aplikasi penjualan berbasis android lebih efesien digunakan untuk masyarakat dalam melakukan proses jual-beli karena lebih familiar dimasyarakat. Maka dari itu pengem-bangan sistem yang dilakukan peneliti adalah aplikasi berbasis android dalam proses penjualan serta untuk meningkatkan penjualan. Metode yang digunakan dalam pengambangan aplikasi android ini adalah prototype dengan beberapa tahapan komunikasi, rencana cepat, pemodelan dan desain cepat, desain cepat, konstruksi prototipe, dan pengiriman dan umpan balik penyebaran. Tujuan dari penelitian ini untuk mempermudah penjualan, meningkatkan penjualan, serta agar proses penjualan lebih efektif, dan efesien. Kata kunci: aplikasi; android; penjualan; UMKM